The pricing of different dimensions of liquidity: Evidence from government guaranteed bonds - Black, Jeffrey R.; Stock, Duane; Yadav, Pradeep K. (Journal of Banking & Finance, 2016)
There are three important dimensions of liquidity: trading costs, depth, and resiliency. We investigate the relevance of each of these three dimensions of liquidity – separately and in conjunction – for the pricing of corporate bonds. Unlike previous studies, our sample allows us to cleanly separate the default and non-default components of yield spreads. We find that each of the above three dimensions of liquidity are priced factors. Overall, in our sample, a one standard deviation change in trading costs, resiliency, and depth measures lead to a change in non-default spreads of 5.00 basis points, 2.27 basis points, and 1.27 basis points, respectively. We also find that both bond-specific and market-wide dimensions of liquidity are priced in non-default spreads. Finally, we find that there does exist in some periods a small residual non-default yield spread that is consistent with an additional “flight-to-extreme-liquidity” premium reflecting investor preference for assets that enable quickest possible disengagement from the market when necessary.